Development of a four-row paddy transplanter by applying value engineering principles. (2018) - Mohan, M.; Sundararaj, G.; Devadasan, S.R.; Murugesh, R.
Engineers and practitioners have been developing manually operated paddy transplanters to enable farmers for achieving productivity and quality in paddy transplantation. These manually operated paddy transplanters are often difficult to be operated. The research reported in this paper was carried out to overcome these difficulties which are experienced by the farmers while operating a six row manually operated paddy transplanter. This exercise was carried out by applying the steps of value engineering job plan. While carrying out this exercise, five ideas generated by a team of experts were implemented in practice. According to one of these ideas, a four row manually operated paddy transplanter was developed from six row manually operated paddy transplanter. Though there is insignificant increase in the manufacturing cost, the developed four-row manually operated paddy transplanter was found to be easier to operate than to operate the six-row manually operated paddy transplanter.